The Urgency of Recognizing Professional Zakat as an Income Tax Deduction in the Indonesian Positive Legal System - Carmadi, Carmadi; Saleh, Mohammad (PAMALI: Pattimura Magister Law Review, 2025)
Introduction: Professional zakat represents a form of actualizing religious obligations that holds significant potential in supporting the socio-economic development of the Muslim community in Indonesia. This research is motivated by the suboptimal utilization of professional zakat as an instrument for reducing income tax (PPh), despite the existence of legal foundations within Indonesia’s positive legal system, such as Law Number 36 of 2008 on Income Tax and Law Number 23 of 2011 on Zakat Management.Purposes of the Research: The purpose of this study is to analyze the legal regulations, implementation, and legal implications of recognizing professional zakat as a deductible component of income tax, with a particular focus on the Amil Zakat Institution Yayasan Dana Sosial Al-Falah (LAZ YDSF) in Malang City.Methods of the Research: This research employs a normative legal method with statutory and conceptual approaches.Results Main Findings of the Research: The findings indicate that although existing regulations provide legitimacy for tax reduction through professional zakat, its implementation still faces several challenges, including low public literacy on legal and taxation matters, and the lack of optimal synergy between tax authorities and zakat institutions. These findings highlight the need for policy reform and digitalization of reporting systems to enable effective, fair, and inclusive integration between zakat and taxation, while promoting dual compliance with both religious and fiscal obligations of the Indonesian Muslim community.